2013
DOI: 10.1007/s11695-013-0891-5
|View full text |Cite
|
Sign up to set email alerts
|

Adjustable Intragastric Balloon vs Non-Adjustable Intragastric Balloon: Case–Control Study on Complications, Tolerance, and Efficacy

Abstract: The idea of dynamic balloon therapy needs to be confirmed with wider series. The rate of complication reported is very high, and several studies regarding safety and efficacy are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
2
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(32 citation statements)
references
References 19 publications
(37 reference statements)
0
27
2
3
Order By: Relevance
“…The mean age of patients using NIBs was 40 and of those using AIBs, 39.7 -numbers higher than those registered in a similar study conducted by Genco et al (17) . The gender variable showed a pattern similar to other studies (17,23) . Females represented 79.9% of the NIB users and 72.4% of the AIB users.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…The mean age of patients using NIBs was 40 and of those using AIBs, 39.7 -numbers higher than those registered in a similar study conducted by Genco et al (17) . The gender variable showed a pattern similar to other studies (17,23) . Females represented 79.9% of the NIB users and 72.4% of the AIB users.…”
Section: Discussioncontrasting
confidence: 50%
“…Intragastric balloon (IGB) use is indicated for patients whose BMI precludes the option of bariatric surgery (8)(9)(10) , who have other contraindications, or who need to lose weight prior to undergoing surgery (10,11) . It is a minimally invasive procedure approved by the Food and Drug Administration (FDA) and Brazilian Public gences in the IGB literature regarding the effects on excess weight loss (%EWL) and BMI reduction, as well as the possible initial influence of BMI on final treatment result (16)(17)(18)(19) . Furthermore, there is a scarcity of nationally or internationally published studies, not only evaluating the results of AIBs and NIBs individually, but also in comparison.…”
Section: Introductionmentioning
confidence: 99%
“…While a 4-month dwell time is less than the 6-month dwell times of other liquid-filled gastric balloons, previous work has demonstrated that 80 % of the weight lost in gastric balloon therapy occurs in the first 3 months of therapy [13]. Moreover, previous studies have demonstrated that balloons can be repeated in patients who require additional weight loss [14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…Gastric balloons are typically made of silicone elastomer [13,31]. One of their modes of failure is related to the gastric environment weakening the material [4,16], which can lead to spontaneous deflation and resultant bowel obstruction [14]. This type of failure is related to the cohesive deterioration of the silicone elastomer, while our study focuses on the adhesion between the silicone rubber and the substrate.…”
Section: The Role Of Lipids and Compression Forces In The Degradationmentioning
confidence: 99%